1994
DOI: 10.1111/j.1439-0329.1994.tb00983.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heavy metals and acid irrigation on the birch rust, Melampsoridium betulinum

Abstract: Effects of simulated acid rain and heavy metals on the occurrence of Melampsoridium betulinum in naturally infected mountain-birch trees and seedlings {Betula pubescens subsp. tortuosa) were studied in a subarctic area where background polution levels are low. The short term (2 years) effects of copper, nickel and sulphuric acid, and long term (8 years) effects of nitric-and sulphuric-acid deposition on birch-rust infection were determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Nevertheless, no correlation among pathogenic RIF and air quality was observed. Some pathogenic fungi that cause specific diseases are favoured by pollutants presence, and they produce a stimulatory effect increasing the disease incidence (Helander 1994;Magan et al 1995). It was previously reported that some tree endophytes are mostly harmless colonizers of healthy plant tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, no correlation among pathogenic RIF and air quality was observed. Some pathogenic fungi that cause specific diseases are favoured by pollutants presence, and they produce a stimulatory effect increasing the disease incidence (Helander 1994;Magan et al 1995). It was previously reported that some tree endophytes are mostly harmless colonizers of healthy plant tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding pathogenic infections, there is not a homogeneous effect of air pollutants on plant diseases. Some pathogenic fungi that cause specific diseases are favoured by pollutants presence, and they produce a stimulatory effect increasing the disease incidence (Helander 1994;Magan et al 1995). Conversely, the incidence of some diseases is decreased by the presence of pollutants, producing an inhibitory effect (Wani et al 1997;Khan et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The isolation of endophytic fungi was done following the protocol described by Helander et al (1994) with some slight modifications. The fragments obtained were washed with sterile distilled water, treated with ethanol (70%) for 2 min followed by rinsing with sterile distilled water.…”
Section: Isolation Of Endophytic Fungimentioning
confidence: 99%